One new species and two new synonyms in the genus Ethmia (Lepidoptera: Elachistidae: Ethmiinae) - Wang, Jing-Jing; Wang, Shu-Xia (Zootaxa, 2012)
One new species of the genus Ethmia Hübner [1819], viz. E. apispinata sp. nov., is described based on the specimenscollected in Yunnan Province; two new synonyms are proposed: Ethmia pseudozygospila Kun & Szabóky, 2000, syn. nov.(= E. guangzhouensis Liu, 1980), and Ethmia amissus Kun, 2001, syn. nov. (= E. pingxiangensis Liu, 1980); the male of E. pingxiangensis is described for the first time. Images of adults and illustrations of genitalia are provided.